Single Nucleotide Polymorphism (SNP) rs2229569 with L Selectin Gene Expression in Iraqi Female during in vitro Fertilization Program. (Baghdad Science Journal, 2024)
Infertility is recognized as one of the leading reproductive health problems in various regions of the world. In vitro fertilization (IVF) is one of the most effective treatments for infertility. In the current research, the role of the selectin -L (SELL) gene, especially the rs2229569 polymorphism, has been determined in terms of implantation and expression level. This work involved 67 females who underwent an in vitro fertilization cycle, divided into two major groups: the implantation failure female group and the implantation success female group. Blood samples were collected from the females. After DNA extraction from blood sample then amplification by polymerase chain reaction, samples were sent for sequence analyses. The SNP rs2229569 was detected and that recorded three genotypes. The failure group had a deviation from H.W.E., and the success group was in agreement with H.W.E. law according to Chi square values (X2 = 11.60, 1.58). Significant differences in the failure group refers to the effects of infertility in the study population. Odds ratio of rs2229569 showed that the T allele was (2.09), so T allele may be considered a risk allele for the failure implantation. Finally, the SELL gene expression had a downregulation in female with failed implantation compared to female in successful implantation groups.